2006
DOI: 10.1063/1.2177426
|View full text |Cite
|
Sign up to set email alerts
|

Carrier dynamics in α-Fe2O3 (0001) thin films and single crystals probed by femtosecond transient absorption and reflectivity

Abstract: Articles you may be interested inTransient reflectivity as a probe of ultrafast carrier dynamics in semiconductors: A revised model for lowtemperature grown GaAs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
184
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 23 publications
23
184
1
Order By: Relevance
“…Clearly, the donor density measurement from the Mott-Schottky analysis is very complex; therefore, the carrier concentrations of the films were also measured using Hall measurements. We found values between 5 9 10 17 and 5 9 10 20 cm -3 , which are within the same range for other reported photoanodes, such as hematite or bismuth vanadate materials [103][104][105]. We also reported on the electronic transport properties (carrier mobility) and spectroscopic measurements (carrier recombination).…”
Section: -9supporting
confidence: 61%
“…Clearly, the donor density measurement from the Mott-Schottky analysis is very complex; therefore, the carrier concentrations of the films were also measured using Hall measurements. We found values between 5 9 10 17 and 5 9 10 20 cm -3 , which are within the same range for other reported photoanodes, such as hematite or bismuth vanadate materials [103][104][105]. We also reported on the electronic transport properties (carrier mobility) and spectroscopic measurements (carrier recombination).…”
Section: -9supporting
confidence: 61%
“…12 Using this assignment, transient absorption (TA) spectroscopic studies have reported shortlived (<100 picoseconds) photocarriers in these materials. [13][14][15][16][17][18][19][20] In contrast to these earlier findings, more recent studies have identified a long-lived (>microseconds) absorption band at 580 nm due to photogenerated holes 21,22 in nanoporous hematite films with reported high incident-photon-to-electron-conversion-efficiency (IPCE).…”
mentioning
confidence: 55%
“…[43] This extremely low value of radiative carrier recombination 436 www.chemsuschem.org suggests that fast nonradiative processes such as carrier trapping and phonon coupling are limiting the excited-state lifetime. [51] Indeed, the ultrafast dynamics of excited states in hematite have been studied in colloidal nanoparticles, single crystals, and even nanostructured thin films using femtosecond laser spectroscopy. [43,[51][52] In nanoparticles it was found that the excited state decay profiles were independent of the pump power and the probe wavelength, and were not affected by lattice doping.…”
Section: Photogenerated Carrier Lifetimementioning
confidence: 99%